2019
DOI: 10.1186/s40900-019-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in designing and conducting doctoral research: the whys and the hows

Abstract: Plain English summary Evidence shows that public and patient involvement in research has a positive effect on its quality and end-results. Thus, public and patient involvement in all stages of research is becoming commonplace. There are limited detailed examples however, that describe how to make this possible, especially for those doing PhD research. Doctoral researchers are often new to research practice or have limited experience and are often bound by strict time and financial constraints. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 24 publications
8
75
0
Order By: Relevance
“…There is little evidence describing PPI in doctoral research [25,26]. Moreover, researchers rarely provide a complete picture of what happened during the research process.…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence describing PPI in doctoral research [25,26]. Moreover, researchers rarely provide a complete picture of what happened during the research process.…”
Section: Discussionmentioning
confidence: 99%
“…Minogue et al [ 38 ] suggested that involving “users” in research would reduce wasted research and enhance the quality of fall-prevention initiatives. According to Tomlinson et al [ 39 ], PPI in research may improve the quality of research projects and strengthen the relevance and impact of research. In addition to these benefits, participants and members of the public reported that they were provided with a mechanism to share their experiences while directly influencing change, empowering them to contribute to society and gain new skills [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The available literature on PPI involving older adults indicates that there are many benefits and challenges of engaging older adults in the research process, but challenges can be overcome. There is a need to build evidence that involvement has a positive impact on research processes 25 , 46 . This paper describes the methodological approach adopted to recruit and establish a PPI panel of older adults, family carers and academic researchers and our plans for describing the process and evaluating its impact on the research panel.…”
Section: Discussionmentioning
confidence: 99%